The cult of saints and the Virgin Mary in medieval Scotland - Boardman, Steve; Williamson, Eila (Boydell & Brewer, 2010)
Of all the Celtic countries, Scotland has lacked the kind of scholarly attention that has been lavished fruitfully on Wales, Ireland, Cornwall and Brittany. And yet of all of them, Scotland offers the widest range of interfaces with broader work on the cult of saints. The papers presented here cover this territory very effectively.... [the book] brings together excellent studies that successfully explore the wide ramifications of the topic. Anyone with an interest in saints' cults will want this book. DAUVIT BROUN, Professor of Scottish History, University of Glasgow. This volume examines the phenomena of the cult of saints and Marian devotion as they were manifested in Scotland, ranging from the early medieval period to the sixteenth century. It combines general surveys of the development of the study of saints in the early and later middle ages with more focused articles on particular subjects, including St Waltheof of Melrose, the obscure early medieval origins of the cult of St Munnu, the short-lived martyr cult of David, duke of Rothsay, and the Scottish saints included in the greatest liturgical compendium produced in late medieval Scotland, the Aberdeen breviary. The way in which Marian devotion permeated late medieval Scottish society is discussed in terms of the church dedications of the twelfth and thirteenth-century aristocracy, the ecclesiastical landscape of Perth, the depiction of Mary in Gaelic poetry, and the pervasive influence of the familial bond between holy mother and son in representations of the Scottish royal family. Dr Steve Boardman is Reader in History, University of Edinburgh; Eila Williamson gained her PhD from the University of Glasgow. Contributors: Helen Birkett, Steve Boardman, Rachel Butter, Thomas Owen Clancy, David Ditchburn, Audrey-Beth Fitch, Mark A. Hall, Matthew H. Hammond, Sim Innes, Alan Macquarrie